Analysis Representation Related to the Activities Relative Values Evaluated Using the Method Job Evaluation through the Load - Nistor Dorin LEONARD (Revista de Management Comparat International)
The results obtained on the relative values for their work evaluated by applying a new job evaluation methods are analyzed in this paper. The research aims to identify whether job evaluation methodology through the tasks ensures relevant data on the relative values of activities. Demonstrating the relevance of data obtained support the further step, namely the job evaluation, on the premise - that assessed the relative values for stations to be correct, it is necessary to advance the tasks to be effectively evaluated. Study is applied in three areas of activity of human resources, financial, production accounting and ointments. I used two samples of professionals (occupants of positions evaluated) and lay persons from different companies. Analyses show that the methodology for assessing the tasks get good results in evaluation activities as a result we can say that the relative values for the right job will be evaluated.